2018
DOI: 10.22374/ijmsch.v1i1.14
|View full text |Cite
|
Sign up to set email alerts
|

“The Environment Was Like They Were in the Pub But With No Alcohol” –

Abstract: Men’s health and life expectancy, particularly for those men from lower socioeconomic groups, remains an issue of concern in Ireland. This concern is reflected in the recent National Men’s Health Action Plan where important priority has been placed on finding appropriate ways to garner sustained involvement in health promotion interventions for men. Physical activity (PA) has been shown to be a useful ‘hook’ to assist with such engagement. ‘Men on the Move’ (MOM) is a 12 week, community-based, gender-sensitise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In total, N = 14/35 quantitative reports [40,43,45,[47][48][49][50][51][52][53][54][55][56][57], N = 7/35 qualitative reports [42,[58][59][60][61][62][63] and N = 14/35 mixed/other methods reports (consisting of service development descriptions, process evaluations, mixed methods case studies, real world trials, impact reports [11,41,44,46,[64][65][66][67][68][69][70] or methods not reported (N = 3/35) [71-73]) were included. Of the quantitative reports, five were randomised controlled trials, five were controlled and uncontrolled before-after studies, and four were pilot/feasibility trials (Table 1).…”
Section: Objective (I): To Identify and Summarise The Scope Of The Li...mentioning
confidence: 99%
See 4 more Smart Citations
“…In total, N = 14/35 quantitative reports [40,43,45,[47][48][49][50][51][52][53][54][55][56][57], N = 7/35 qualitative reports [42,[58][59][60][61][62][63] and N = 14/35 mixed/other methods reports (consisting of service development descriptions, process evaluations, mixed methods case studies, real world trials, impact reports [11,41,44,46,[64][65][66][67][68][69][70] or methods not reported (N = 3/35) [71-73]) were included. Of the quantitative reports, five were randomised controlled trials, five were controlled and uncontrolled before-after studies, and four were pilot/feasibility trials (Table 1).…”
Section: Objective (I): To Identify and Summarise The Scope Of The Li...mentioning
confidence: 99%
“…When screening the record for eligibility, three reports were associated with this record, all of which met the review inclusion criteria. Therefore, all three reports were sought for retrieval, assessed for eligibility, collated and reported as The Men on the Move study [40][41][42]. †N = 35 reports of N = 28 individual studies were included.…”
Section: Objective (I): To Identify and Summarise The Scope Of The Li...mentioning
confidence: 99%
See 3 more Smart Citations